THE EFFECTIVENESS OF ROLE PLAYING METHOD ON STUDENTS’ SPEAKING DESCRIPTIVE TEXT ABILITY - Kristina Magdalena Lumbantobing; Miranda Gultom; Zahwa Naurah Fadhilahi; Fadhillah Nursakinah; Fatimah Junita Nasution; Lasma Rohana Siregar (Jurnal Education and Development, 2026)
The aims of this study are: to what extent is the application of the role playing method in teaching speaking descriptive text ability, to what extent are students’ speaking descriptive text ability before and after using role playing method, then to what extent there is a significant effect of role playing method on students’ speaking descriptive text ability at the seventh grade of SMP Negeri 4 Padangsidimpuan. The method used is the one group pre-test post-test experiment with a sample of 32 students (taken through purposive sampling from 362 students). Data was collected through observation and tests. The result show that the application of the role playing method reaches 85%.(good category). The mean score of students’speaking descriptive text ability before and after using role playing method were 43.19 (bad category) and 78.53 (good category). Then, there is a significant effect of role playing method on students speaking descriptive text ability at the seventh grade of SMP Negeri 4 Padangsidimpuan because the table paired sample t-test pretest and pos-test is lower than 0.05(0.000<0.05). it means that hypothesis (Ha) is accepted.